Implementation of Pancasila Education on Students' Democratic Attitudes in the Multiethnic Environment of Mataram City - Yorman (ARMADA : Jurnal Penelitian Multidisiplin, 2024)
This research aims to analyze the implementation of Pancasila Education in shaping students' democratic attitudes in the multiethnic environment of Mataram City. Mataram City is known as a plural area with various ethnicities, cultures, and religions that coexist. In this context, Pancasila Education is an important instrument to instill the values of tolerance, equality, and respect for differences. The research method used is qualitative descriptive with data collection techniques through interviews, observations, and documentation studies in several secondary schools. The results of the study show that the implementation of Pancasila Education has made a significant contribution to increasing students' awareness of the importance of democracy, tolerance, and active involvement in deliberation. However, there are still challenges in the form of the influence of social media, the lack of integration of Pancasila values in extracurricular activities, and differences in students' family backgrounds. This study concludes that Pancasila Education plays a strategic role in shaping the democratic character of students, so it is necessary to innovate project-based learning methods and contextualize Pancasila values with students' daily lives.